1973
DOI: 10.1039/p29730001565
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the permanganate oxidation of unsaturated compounds. Part III. Intermediates in the oxidation of maleic and fumaric acids

Abstract: The intermediates in the permanganate oxidation of maleic and fumaric acids have been studied in acidic solutions, The accumulation and decay of manganese(ti1) has been demonstrated by the stopped-flow technique. The concomitant four-electron oxidation of the substrates leads to the formation of forrnyl( hydroxy)acetic acid. The subsequent reactions reveal a complex pattern in which hydroxymalonic. glyoxylic, and oxalic acid are further intermediates. The product distribution has been determined as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The inorganic Mn­(III) disproportionates to Mn­(II) and Mn­(IV) due to the absence of any stabilizing agent in the reaction mixture . Besides, a peak at 486 nm corresponding to Mn­(III) is not observed during the entire oxidation process, which further supports the finding.…”
Section: Results and Discussionsupporting
confidence: 72%
“…The inorganic Mn­(III) disproportionates to Mn­(II) and Mn­(IV) due to the absence of any stabilizing agent in the reaction mixture . Besides, a peak at 486 nm corresponding to Mn­(III) is not observed during the entire oxidation process, which further supports the finding.…”
Section: Results and Discussionsupporting
confidence: 72%
“…However, manganese(III) can be stabilized by a number of ways including: (i) increased acidity; (ii) increased manganese(II) concentrations; and (iii) the presence of complexing agents . A large molar excess of pyrophosphate over manganese(III) has been shown on numerous occasions , to effectively “trap” this species and prevent its disproportionation during the permanganate reduction pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This debate was mainly due to the complexity of the reaction intermediates, such as Mn(III), -(IV), -(V) and -(VI) species involved with permanganate reduction (Bose et al, 1991). There have been extensive studies on the mechanisms of permanganate oxidation of various organic compounds, with efforts to identify the reaction intermediates (e.g., Jáky and Simándi, 1972;Jáky et al, 1973;Lee and Brownridge, 1973;Simándi et al, 1977;Bose et al, 1991). Previous studies have shown that short-lived manganese intermediate species were not only very reactive but also subject to disproportionation.…”
Section: Introductionmentioning
confidence: 99%